Classic branding and new perspectives : moving from brand as reference to brand as personality to brand as icon. - Chua, Matthew Han Ming. (2008)
In this study, consumer behavioral explanations are sought to support the conceptual soundness and benefits of the Goodyear model to brand managers. Two separate sub-studies are undertaken, corresponding to two different stages of the Goodyear model.